Genetic Engineering in the Twenty-First Century: Genetically modified organisms - Conrad B Quintyn (Global Journal of Ecology - Peertechz Publications, 2021)
In agriculture, animals and plants are engineered to produce pharmaceuticals, and crops are modified to be nutritious, tolerant of herbicides and the natural environment, and resistant to disease. While these goals may seem practical, is it wise to modify plant systems without a clear idea of the long-term effects of genetic engineering in animals and humans? [1].